Ethical Leadership toward Job Involvement among Manufacturing Exempt Staff in Penang - Nasina MAT DESA; Muhammad Hasmi ABU HASSAN ASAARI; Kumaran KOOTHA PERUMAL (Communications of International Proceedings, 2020)
Job involvement among employees is vital in the organization as it works as internalizing values of goodness and importance of working among people around them. Ethical behavior needs to start with leaders within the organization. The importance of ethical leadership as the driving force for ethical practices can’t be underestimated. Meanwhile, perceived organizational support is vital in an organization to maximize the involvement of employees. The objective of this paper is to examine the relationship and impact of ethical leadership and job involvement among manufacturing employees. A total of 250 self-administered questionnaires were distributed among exempt staff of a manufacturing organization in Penang, Malaysia. They are the employees who are exempted from minimum wage, overtime regulations, and other rights and protections in the organization. Data analysis such as demographic, reliability, correlations, and regression was done. The finding of the paper reveals that ethical leadership can affect job involvement among staffs in the manufacturing organization. If ethical leadership are not practiced by the organization’s management, then they are likely to face issues on their employees’ job involvement. Hence, the findings in this paper help the organization in finding a way of dealing with their exempt staff to make them work better in their organization.